Socio-Demographic and Eco-Epidemiological Parameters of Tick-Borne Infections Morbidity in Baikal Region - O. V. Mel’nikova; N. A. Bykova; N. V. Ustinova; E. I. Andaev (Проблемы особо опасных инфекций, 2024)
The aim of the work was to compare the main socio-demographic and eco-epidemiological parameters of tick-borne viral encephalitis, tick-borne borrelioses and tick-borne rickettsiosis.Materials and methods. The authors’ databases based on epidemiological investigation records were used for the study. All in all, 2974 cases (Irkutsk and the Irkutsk district) were analyzed during the periods of 1995–2022 for tick-borne viral encephalitis and tick-borne borrelioses, and 2001–2022 for tick-borne rickettsiosis.Results and discussion. The following parameters were assessed: the timing of epidemic season; the geography of prevalence; localization of tick bite on the human body; incubation time; gender and age structure of patients; social composition and exposure conditions. It was shown, that the parameters had their own features for each disease, and part of them are common to all Eurasian area of these infections. The shared characteristics include: the early epidemic season onset for tick-borne rickettsiosis; the shorter incubation time for tickborne rickettsiosis as compared to tick-borne viral encephalitis and tick-borne borrelioses; the increased frequency of tick-borne rickettsiosis vectors’ bites near the head and neck, and tick-borne borrelioses vectors – on the torso; large percentage of older persons among patients with tick-borne borrelioses and children under 14 years of age among patients with tick-borne rickettsiosis; prevalence of male population over female one as regards all surveyed pathogens. Low incidence of tick-borne diseases among professional contingent (the work associated with staying in natural foci of infection), an increased risk of tick-borne encephalitis and rickettsiosis among social group “unemployed”, and tick-borne borrelioses – among retirees, can be attributed to regional specificity.